Impact of tobacco smoking, betel quid chewing and alcohol consumption habits in patients with oral cavity cancer in Bangladesh - Debnath, Kala Chand; Uddin, Md Sahab; Goswami, Srijan; Herrera-Calderon, Oscar; Kabir, Md Tanvir; Hasan, Md Fakhrul; Lucky, Kamrun Nahar; Khanum, Sayema; Abdel-Daim, Mohamed Mohamed (© 2017, Asian Network for Scientific Information, 2018)
This article was published in the Journal of Medical Sciences [© 2017, Asian Network for Scientific Information] and the definite version is available at : http://doi.org/10.3923/jms.2017.46.52 The Journal's website is at: https://scialert.net/abstract/?doi=jms.2017.46.52